Scale Development, Validation and Use of Structural Equation Modelling to Test the Impact of Consumer Confidence and Persuasibility on Dissonance - Parumasur, Sanjana Brijball; Parumasur, Nabendra (Journal of Economics and Behavioral Studies, 2016)
This study develops and validates a scale to assess the impact of consumer confidence and persuasibility on dissonance and applies the instrument to high-end consumers. It also assesses the relationship between consumer confidence and persuasibility as these constructs merge to influence dissonance. A sample of 200 new motor vehicle buyers who purchased from a leading and reputable motor vehicle company in KwaZulu-Natal, South Africa, was drawn using stratified random sampling based on range of motor vehicle (bottom, middle, top). Initially, exploratory factor analysis (EFA) was used to extract the factors. The reliability of the modified questionnaire was then assessed using Cronbach’s Coefficient Alpha. Thereafter, confirmation factor analysis (CFA) was undertaken to develop and test the model structure in SEM, which generated a good model fit. Pearson r was computed to assess the relationship amongst the dimensions. Using structural equation modelling, the results support a significant relationship between consumer persuasibility and dissonance and a significant but inverse relationship between consumer confidence and dissonance, and confidence and persuasibility respectively.